Karakteristik Hak Kebendaan Pada Objek Jaminan Fidusia Berupa Benda Persediaan - Widjaja, Erich Kurniawan; Putra, William Tandya (JURNAL MERCATORIA, 2019)
Inventory as a fiduciary object has different law consequences towards bank as the fiduciary receiver and as the third party. This what made the researcher interested to conduct a research to investigate the property right characteristic of the inventory as a fiduciary object through statute approach and conceptual approach. This research has found that some property right characteristic do not stick with the inventory or supplies since its characteristic is not always the same. One of the intangible characteristic of the property right is “droit de suite” or the characteristic that follows wherever the fiduciary object be. The absence of property right characteristic of inventory fiduciary object cause the weakening of that property right which is known as relativering.